Environmental Care Education through the Plastic Waste Reduction Movement in Realizing Environmentally Friendly Schools - Wunarlan, Irwan; Yusuf, Nilawaty; Pongoliu, Yayu Isyana D. (Society : Jurnal Pengabdian Masyarakat, 2026)
The problem of plastic waste is an environmental issue that is also faced by the elementary school environment. The partner of this service activity, namely SDN 6 Suwawa, Bone Bolango Regency, shows the low condition of students' awareness of the impact of plastic waste and the still high habit of using single-use plastics in daily activities at school. This condition has the potential to hinder the realization of a clean and environmentally friendly school environment. This community service activity aims to increase knowledge and foster an attitude of caring for the environment in students through education on reducing plastic waste from an early age. The method of implementing the activity uses an environmental education socialization approach which is carried out interactively through the delivery of materials, discussions, and simple reflections on the impact of plastic waste and environmentally friendly behaviors that can be applied by students. The results of the activity showed an increase in students' understanding of the negative impact of plastic waste on the environment, accompanied by a change in positive attitudes in the form of a commitment to dispose of waste in its place, reducing the use of single-use plastics, and starting to get used to environmentally friendly behavior at school. Overall, this activity made an initial contribution in supporting the realization of environmentally friendly schools through changing students' knowledge and attitudes towards plastic waste management.